An evaluation of the genotoxicity and 90‐day repeated dose oral toxicity in rats of Porphyridium purpureum - Murbach, Timothy S.; Glávits, Róbert; Endres, John R.; Hirka, Gábor; Vértesi, Adél; Béres, Erzsébet; Pasics Szakonyiné, Ilona (Journal of applied toxicology, 2024)
Interest in microalgae products for use in food is increasing, as demands for sustainable and cost‐effective food choices grow due to the escalating global population and increase in climate‐related struggles with agriculture. Toxicological assessments of some species of microalgae have been conducted, but there were little data available for the oral consumption of the red microalgae Porphyridium purpureum and no data on genotoxicity. This article articulates a genotoxicity assessment and a 90‐day repeated dose oral toxicity study in rats performed according to OECD guidelines. Under the experimental conditions applied, the test item did not induce gene mutations by base pair changes or frameshifts in the genome of the strains used in the bacterial reverse mutation test. Similarly, the test item did not induce structural chromosomal aberrations in V79 hamster lung cells. The test item also did not cause chromosomal damage in bone marrow of mice in the mammalian micronucleus test. The no observed adverse effect level (NOAEL) of the 90‐day repeated dose oral toxicity study in rats was determined to be the highest dose tested, 3000 mg/kg bw/day. These data add to the body of evidence regarding the safety of P. purpureum for human consumption. There is interest in the use of microalgae in food. Many species have been studied and are currently used in food products sold around the world, but little safety data are available for Porphyridium purpureum. This species was used as a test item in a 90‐day repeated dose oral toxicity study in rats as well as a genotoxicity assessment. The no observed adverse effect level was the highest dose tested, 3000 mg/kg bw/day, and it did not induce genotoxic changes.